A Novel Cross-Priming Amplification-Based Assay for Tuberculosis Diagnosis in Children Using Gastric Aspirate - Quan, Shuting; Jiang, Tingting; Jiao, Weiwei; Zhu, Yu; Liao, Qiong; Liu, Yang; Fang, Min; Shi, Yan; Duan, Li; Shi, Xiaomei; Wang, Yacui; Tian, Xue; et al. (Frontiers in Microbiology, 2022)
Low detection rates of Mycobacterium tuberculosis (MTB) by culture and smear microscopy prevent early diagnosis of tuberculosis (TB) in children. Therefore, developing rapid and accurate diagnostic techniques is critical to achieving the global aim of minimizing childhood TB. The present study was performed to evaluate the diagnostic effectiveness of the novel cross-priming amplification-based EasyNAT MTB complex assay (EasyNAT) in childhood TB. Five hundred and six children with suspected TB were enrolled from January 2018 to October 2021. Gastric aspirate (GA) samples were tested by bacterial culture, acid-fast bacillus microscopy, EasyNAT, Xpert MTB/RIF (Xpert) or Xpert MTB/RIF Ultra (Xpert Ultra). Among 239 children simultaneously tested by EasyNAT and Xpert methods, both assays showed similar sensitivities in total active TB cases (22.6% [31/137] vs. 26.3% [36/137], P=0.441) and in bacteriologically-confirmed TB cases (both 61.5% [16/26]). The two assays presented similar specificities of 98.1% (100/102) and 99.0% (101/102), respectively (P=1.000). Among 267 children who were simultaneously tested with EasyNAT and Xpert Ultra, Xpert Ultra demonstrated higher sensitivity than EasyNAT in total active TB cases (50.9% [89/175] vs. 30.3% [53/175], P<0.001). EasyNAT and Xpert Ultra yielded similar specificities, at 97.8% (90/92) and 100.0% (92/92), respectively (P=0.155). These findings indicated that Xpert Ultra was superior to EasyNAT despite its higher cost and EasyNAT was not inferior to Xpert in the diagnosis of childhood TB using GA samples. EasyNAT may therefore be a suitable alternative diagnostic method for childhood TB based on its cost-effectiveness, speed, and accuracy.